ANYNYALA: DEVIATIONS IN THE GENERAL PATTERN OF THE MARRIEGE SYSTEM IN THE SOCIETY OF GOWA REGENCY - Sri Wulandari; Abdul Rahman A Sakka; Bakhtiar Bakhtiar (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to (1) identify the factors underlying the occurrence of anynyala in the marriage system, (2) understand the negotiation process undertaken by families in resolving anynyala issues, and (3) explore the social and psychological impacts experienced by the individuals and families involved. Using a qualitative approach, this study seeks to provide insight into the social and cultural dynamics underlying this practice. Data collection techniques were conducted through observation, interviews, and documentation. The technique for checking the validity of the data used member checks, the data analysis techniques used were data reduction, data presentation, and conclusions. The research findings indicate that the anynyala phenomenon in Sengka Village is triggered by several factors, including social and economic pressures and the inability to meet high dowry demands. Furthermore, the negotiation process between the two families is often fraught with tension, but it can potentially resolve the conflict in a mutually beneficial manner. The study also found that individuals and families involved in anynyala experience social stigma and prolonged psychological burdens, which can impact their social relationships within the community.